ENHANCING THE PRODUCTIVITY OF DEGRADED LAND THROUGH SOIL AND WATER CONSERVATION TECHNIQUE IN CARITA RESEARCH FOREST, WEST JAVA - Pratiwi, Pratiwi; Narendra, Budi Hadi (Indonesian Journal of Forestry Research, 2012)
Encroachments on Carita Research Forest area have exacerbated the degradation of land due to uncontrolled runoff, erosion and nutrient losses especially on the sloping land with high annual rainfall. To reduce the severity of the degradation the area should be rehabilitated by applying soil and water conservation techniques. The techniques used were the vegetative methods (culture), and a combination of it with mechanical/technical methods. The combination method is expected to be more effective in controlling runoff, erosion and nutrient losses. One important parameter is the efficiency of the distance of the vertical mulch channel, which affects the application cost. This study was aimed to determine the effect of different distances of vertical mulch channels on the plant growth and annual crop yield as well as its effectiveness in controlling runoff, erosion and nutrient losses. The research was conducted in Carita Research Forest from 2005 to 2008, using the randomized block design. Treatments applied were: vertical mulch with six and twelve meter distances of plots of khaya (Khaya anthotheca C.Dc.) and corn ( Zea mays L.) cropping system. Observations included height and diameter growth of khaya, runoff and erosion, and cost per ha. The results showed that six meter of vertical mulch was the most efficient distance. The height and diameter of khaya tree increased by 7% and 31% in six meter distance compared to the control. Moreover, runoff and erosion was reduced by 75% and 37%, and nutrient losses could be trimmed down by three to five times. In addition, six meters distance could also produce corn of 712 kg/ha/year, which was 73% greater than corn production without vertical mulch. On the other hand, the cropping system with six meter distance of vertical mulch required Rp 3,250,000,- per ha, which was Rp 250,000,- more expensive than that without vertical mulch.